BUDGET NORMALIZATION AND PRICING FEATURES IN CONSTRUCTION - M. I. Gadzhieva; A. M. Esetova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
It is proved that the pricing of the construction is different from the pricing system in the industry and other branches of economy, because it has different methodological and organizational approaches. It has been determined that the cost of construction is set on the stage of its design, in the process of concluding investment contracts (construction contracts), as well as directly during construction, major repairs of objects of capital construction, reconstruction and the implementation of certain types of construction and installation works. It has been found that the pricing mechanism in construction is based on the detailed legal and reference documents regulating material consumption rates and prices, taking into account sectoral, territorial and seasonal features of building production. It has been found that under inflation conditions the price index calculation of construction products for investment purposes is of great importance. Mandatory approval of all stakeholders of the construction production method for determining the price of the construction site is proposed.